PERHITUNGAN HARGA POKOK PRODUKSI PADA CV. LAS ETAM - Fauzaniey, ogi (EKONOMIA, 2013)
OGI FAUZANIY, Calculation of Cost of Production In the CV. Las Etam. Under the guidance of Mr. Robin Jonathan and Mrs. Elfreda.Based on the research results of the cost of production by using activity-based costing to manufacture products canopi types of IDR. 2,993 million, iron fence of IDR 3,328,083, and trails of IDR 2,521,333. of the results obtained can be compared to the difference in prices, the cost of production with the results of calculations using activity-based costing approach.Based on the analysis and discussion it was concluded that the difference in price is due to the activity based costing method, charging overhead costs to each product. On overhead cost accounting method for each product is only charged at cost driver alone. As a result, there tends to be distortion on the overhead loading. While the ABC method, overhead costs for each product are charged to cost a lot of drivers. So that the ABC method, have been able to allocate costs to each activity based on the consumption of the product of each activity. Then the hypothesis is acceptedÂ